2021
DOI: 10.55002/mr.1.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of certain antioxidants-electrolyzed reduced water, tocotrienol and vitamin E in heat-induced oxidative damage and performance in broilers

Abstract: This study was designed to examine the anti-oxidative effect of electrolyzed reduced water, tocotrienol and vitamin E on heat-induced oxidative damage and performance in an experimental model in broilers. On day 12, broiler chickens were subjected to one of the following dietary groups; (i) basal diet and untreated drinking water (control), (ii) basal diet and electrolyzed reduced drinking water (ERW), (iii) basal diet supplemented with 2% rice bran scum oil (as a source of tocotreinol) and untreated drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…More recently we found that chronic heat stress impairs anti-oxidation capacity, and enhances lipid peroxidation in the skeletal muscle of broiler chickens (Azad et al, 2010a).This cellular hazardness further leads to suppressing growth performance, indicating that active oxygen species could mediate in the growth retardation process of stressed birds. This active oxygen species may be reversed by ERW supplementation, because this water contains large amount of active hydrogen that was already proved as an effective scavenger for H 2 O 2 , superoxide, and hydroxyl radical (Shirahata et al, 1997;Tsai et al, 2009a;Azad et al, 2013;2021). Several lines of evidence also indicate that ERW had the ability of a scavenger free radical, such as H 2 O 2 , the hydroxyl radical, and the superoxide radical, to protect DNA, RNA, proteins, cells, and tissues against strong oxidative stress (Shirahata et al, 1997;Huang et al, 2003;Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently we found that chronic heat stress impairs anti-oxidation capacity, and enhances lipid peroxidation in the skeletal muscle of broiler chickens (Azad et al, 2010a).This cellular hazardness further leads to suppressing growth performance, indicating that active oxygen species could mediate in the growth retardation process of stressed birds. This active oxygen species may be reversed by ERW supplementation, because this water contains large amount of active hydrogen that was already proved as an effective scavenger for H 2 O 2 , superoxide, and hydroxyl radical (Shirahata et al, 1997;Tsai et al, 2009a;Azad et al, 2013;2021). Several lines of evidence also indicate that ERW had the ability of a scavenger free radical, such as H 2 O 2 , the hydroxyl radical, and the superoxide radical, to protect DNA, RNA, proteins, cells, and tissues against strong oxidative stress (Shirahata et al, 1997;Huang et al, 2003;Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus it can be hypothesized that antioxidant that possess not only ROS-scavenging ability but also energy producing ability could promote production performance by reducing ROS production. With that point of view, it was already proved the characteristics of electrolyzed-reduced water as a potent antioxidant which could effectively scavenge hydrogen peroxide, superoxide and hydroxyal radical, and protect DNA, RNA, proteins, cells, and tissues under strong oxidative stress conditions (Shirahata et al, 1997;Lee et al, 2006;Tsai et al, 2009a;Park et al, 2009;Azad et al, 2021) and the results of Kajiyama's study also suggest that this water could improve lipid and glucose metabolism in patients with type 2 diabetes or impaired glucose tolerance. Moreover, various biological effects of electrolyzed-reduced water have been reported such as anti-diabetic effect (Kim and Kim, 2006;Jin et al, 2006), growth-stimulating effect of fetus (Watanabe, 1995), and growth-stimulating effect of anaerobic microflora in the human intestine (Vorobjeva, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, researchers had tried to increase the shelf life of meat and meat products through different processes such as refrigeration (Akhter et al, 2022;Rahman et al, 2017), curing (Woods et al, 2019), Drying (Akhter et al, 2009), irradiation (Sadakuzzaman et al, 2021;Haque et al, 2017;Rima et al, 2019;Islam et al, 2018Islam et al, , 2019Islam et al, and 2021, through adding electrolyzed water (Azad et al, 2021) and by adding natural antioxidants (Ali et al, 2022;Hossain et al, 2021;Bithi et al, 2020;Disha et al, 2020;Saba et al, 2018;Jahan et al, 2018;Siddiqua et al, 2018). Now-adays different preservation methods of meat have been developed for short time preservation in the world.…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods for meat and meat by-products preservation such as refrigeration (Akhter et al, 2022;Rahman et al, 2017), curing (Woods et al, 2019), Drying (Akhter et al, 2009), irradiation (Sadakuzzaman et al, 2021;Haque et al, 2017;Rima et al, 2019;Islam et al, 2018Islam et al, , 2019Islam et al, and 2021, through adding electrolyzed water (Azad et al, 2021) and by adding natural antioxidants (Ali et al, 2022;Boby et al 2021;Hossain et al, 2021a;Bithi et al, 2020;Disha et al, 2020;Saba et al, 2018;Jahan et al, 2018;Siddiqua et al, 2018). Refrigeration is a common method of storage meat and meat products to retard the growth of microorganisms and widely used by the sales man in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%